PENGARUH LATIHAN COPING WITH STRESS TERHADAP RISIKO BUNUH DIRI PADA REMAJA DI SMP KASIH KOTA DEPOK TAHUN 2010 - Tinneke A. Tololiu; Budi Anna Keliat; Etty Rekawati (POLTEKKES KEMENKES MANADO, 2012)
Coping with stress exercise program is one form of mental health services, community-based youthheld at the school. The purpose of this study is to get a view of the influence of coping with stressexercise program against the risk of suicide among adolescents in junior high school love of Depok.Design research is a